Aplica????o do design thinking integrado com m??todos ??geis na gest??o de projetos de software - Pereira, Julio Cesar (2018)
The use of an agile method in software development projects looks for a faster delivery of new functionalities through a better change management and increasing the productivity of the team responsible for the software. During the project software development life cycle, the development team is expected to fully understand customers' needs, but it is challenged by geographic constraints, narrow project schedule, or short budget. Design Thinking (DT) is an approach that promotes the understanding of customer needs, considering what is technically and economically feasible. The purpose of this research is to evaluate how DT can be integrated with agile method in software development projects. Design Science Research was the research method chosen and interviews and focus groups have been used to collect data, making it possible to develop a qualitative analysis. The research began with interviews in a software development company to identify existing problems when the agile management had been used in software projects and assess whether using a method that integrates DT approach and agile methods would solve them. Although a method that integrates DT with agile methods was not found in the literature, several models were found that were analyzed in detail, generating the proposal of a method to solve the problems investigated in the company which has software development as a main business, considering both contractor and client perspective. Agile Design is the name of the method created in this research. It will promote the approach of customers, users and project team, involving them in various stages of software development projects. In this way, the integrated approach pursues to enhance the quality of the software delivered, and consequently a higher level of user satisfaction. The theoretical contribution is to prescribe a method based on the aspects founded in the existing models and enable the use in software development projects performed by different organizations. Hence, the proposed method consists in a practical contribution aimed to help organizations facing problems in software development projects, directing it to be flexible, agile and to satisfy the needs of its clients and software users.